2017
DOI: 10.3389/fpubh.2017.00270
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Summer Learning Loss in the UK—Implications for Holiday Club Provision

Abstract: This study sought to examine whether summer learning loss occurs in spelling and word reading in a population of 77 primary school aged children aged between 5 and 10 years (37 boys, mean age 100 months, SD 18 months, and 40 girls mean age 103 months, SD 16 months) attending three schools in areas of low socioeconomic status in Scotland and the North East of England. Word reading and spelling was measured using the word reading and spelling subtests of the Wide Ranging Achievement Test. Participants were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Achievement gaps leave the poorest socioeconomic groups lagging behind their more affluent peers ( 18 ). school narrows these gaps but the gap widens over the long summer holiday ( 19 ). Evidence is limited regarding the impact of other types of school closures on learning loss.…”
Section: School Closures and Academic Developmentmentioning
confidence: 99%
“…Achievement gaps leave the poorest socioeconomic groups lagging behind their more affluent peers ( 18 ). school narrows these gaps but the gap widens over the long summer holiday ( 19 ). Evidence is limited regarding the impact of other types of school closures on learning loss.…”
Section: School Closures and Academic Developmentmentioning
confidence: 99%
“…Although the evidence base surrounding holiday hunger is limited, research with parents has shown that some face more financial difficulties and struggle to provide additional food and activities for their children during the school holidays compared to term time (Defeyter, Graham & Prince, 2015;Gill & Wellington, 2003). Furthermore, Shinwell and Defeyter (2017) recently reported that children's spelling performance declines significantly during the six-week summer break from school; a decline that might be attributable to a lack of nutritious food and enrichment activities during the school holidays. This loss in learning leaves teachers needing to set time aside to support children to catch up academically on their return to school after the holidays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Holiday hunger is likely to have a detrimental effect on school children’s educational performance, health and wellbeing. Although there are common issues with measurement of changes in educational attainment, gaps in attainment between US children in high and low poverty schools which increase across the summer have been reported [6], with summer learning loss also being evidenced among low socioeconomic status (SES) school children in the UK [7]. Moreover, food insecurity is associated with poorer health status and emotional wellbeing [8].…”
Section: Introductionmentioning
confidence: 99%